Genetic criticism in the edition of ‘classics’ (Prassi Ecdotiche della Modernità Letteraria, 2017)
Maria Teresa Giaveri is the curator of many volumes of ‘complete works’ published in Italy and in France. In this paper she focuses on Mondadori’s «I Meridiani» and «Classici Bompiani», two collections similar to the French «Bibliothèque de la Pléiade» by Gallimard; in both of them she faces editorial problems strictly connected to the thems of our journal.
Keywords: Bibliothèque de la Pléiade; Meridiani Mondadori; genetic criticism; editorial choises